FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - LOVARIA LIBRANIA; FRISKA FIRNANTI; Dicky Supriatna (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2021)
This study aims to determine the relationship between institutional ownership, audit committee, independent board of commissioners, leverage, company size, audit quality, and profitability of tax avoidance in manufacturing companies listed on the Indonesia Stock Exchange (IDX). The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) from 2017 to 2019 using the purposive sampling method. The analytical method used is a multiple linear regression model and based on predetermined criteria, a sample of 81 companies is obtained with a total of 243 data companies. The results obtained from the research that profitability has a positive effect on tax avoidance. On the other hand, audit committee, board of commissioners, institutional ownership, leverage, company size, and audit quality do not affect tax avoidance. With the existence of a high level of profitability, the tax burden that must be paid by the company is increasing and encouraging companies to practice tax avoidance.